The ghost orchid [large type] - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels., 2024)
"Psychologist Alex Delaware and Detective Milo Sturgis are faced with their most perplexing case yet when a double homicide investigation leads them to stolen identities and long-buried secrets worth killing for in this riveting thriller from the #1 New York Times bestselling author"--